Knowledge and Participation of Students of the Faculty of Tarbiyah Teacher Training, North Sumatra State Islamic University in the 2024 Election in Indonesia - Annisa, Nur; Saleh, Syarbaini (Yayasan Ilomata, 2024)
This research aims to determine the knowledge and participation of students at the Faculty of Tarbiyah and Teacher Training towards the elections in Indonesia in 2024. The research method used is a qualitative technique with a phenomenological approach, which includes interviews, observation and documentation. The results of the research show that the majority of Faculty of Tarbiyah Teacher Training, State Islamic University of North Sumatra students knowledge level shows that they have sufficient knowledge about the 2024 elections, as well as the majority of students who have sufficient knowledge about the 2024 elections and show active participation. This active participation is influenced by political education and campaigns on campus, although there are groups of students who are easily influenced by the lure of material.